Time to talk about work‐hour impact on anesthesiologists: The effects of sleep deprivation on Profile of Mood States and cognitive tasks. Issue 1 (12th November 2015) - Saadat, Haleh; Bissonnette, Bruno; Tumin, Dmitry; Thung, Arlyne; Rice, Julie; Barry, N'Diris; Tobias, Joseph
Summary: Background: A physician's fatigue raises significant concerns regarding personal and patient safety. Effects of sleep deprivation on clinical performance and the quality of patient care are major considerations of today's health care environment. Aim: To evaluate the impact of partial sleep deprivation after a 17‐h overnight call (3 pm–7 am) on the mood status and cognitive skills of anesthesiologists in an academic clinical hospital setting, as compared to these parameters during regular working hours. Methods: Taking circadian rhythm into account, the following measures were assessed in 21 pediatric anesthesiologists at two time points over the course of the study; (i) between 7 and 8 am on a regular non call day, and (ii) between 7 and 8 am after a 17‐h in‐house call (3 pm–7 am). Six mood states were assessed using the Profile of Mood States. A Total Mood Disturbance (TMD) score was obtained as the sum of all mood scores minus vigor. The total score provides a global estimate of affective state. Simple cognitive tests were similarly administered to assess cognitive skills. A two‐tailed paired t ‐test was used to compare data between regular and post call days. A P < 0.05 was used. Results: The study cohort included 21 pediatric anesthesiologists at a tertiary care children's hospital. Tension, anger, fatigue, confusion, TMD, irritability, feeling jittery, and sleepiness were significantly affected ( P < 0.05). A decrease in vigor, energy, and confidence was observed after a night call shift ( P < 0.05). There was also a decrease in being "talkative" after the call shift ( P < 0.05). Conclusion: Partial sleep deprivation affects the total mood status of anesthesiologists and impacts their cognitive skills. These findings are particularly relevant in a context of increased work expectation, particularly on clinical performance in our modern medical system. Such observations suggest that there may be changes that impact the safety of our patients and the quality of health care that is provided. Abstract :